A comparative study on the in-vitro antibacterial behaviour of chemically-modified calcium phosphate coatings. (14th October 2020) - Qiu, Xihe; Lim, Poon Nian; Thian, Eng San
ABSTRACT: Drop-on-demand (DoD) micro dispensing technique, which enabled nano apatite crystals including hydroxyapatite (HA), silicon-substituted HA (SiHA), silver-substituted HA (AgHA) droplets to be deposited on glass substrate with precise placement, size, and number of droplets was presented in this work. Multi-material coatings containing SiHA:AgHA = 1:3 (1SiHA-3AgHA) were fabricated for obtaining favourable bioactivity and enhanced antibacterial properties. The antibacterial effect of 1SiHA-3AgHA towards Escherichia coli (E. coli) indicated a delayed exponential growth for up to 24 h, with significantly less bacteria adhesion compared to HA and SiHA coatings. The biological response of adipose-derived mesenchymal stem cells (hASCs) cultured on 1SiHA-3AgHA coatings exhibited enhanced cell attachment, proliferation and differentiation, as compared to HA and AgHA coatings. Hence, DoD micro deposition technique could be potentially used in producing multi-material coatings for biomedical applications.